2021
DOI: 10.3390/ijms22042130
|View full text |Cite
|
Sign up to set email alerts
|

Hemidesmosome-Related Keratin Filament Bundling and Nucleation

Abstract: The epithelial cytoskeleton encompasses actin filaments, microtubules, and keratin intermediate filaments. They are interconnected and attached to the extracellular matrix via focal adhesions and hemidesmosomes. To study their interplay, we inhibited actin and tubulin polymerization in the human keratinocyte cell line HaCaT by latrunculin B and nocodazole, respectively. Using immunocytochemistry and time-lapse imaging of living cells, we found that inhibition of actin and tubulin polymerization alone or in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
3
10
0
Order By: Relevance
“…Since integrin β4 binds to the keratin cytoskeleton and to the surrounding substrate, it can be understood as a “docking site” for the keratin network to the substrate 59 . This incorporation will have two effects.…”
Section: Resultsmentioning
confidence: 99%
“…Since integrin β4 binds to the keratin cytoskeleton and to the surrounding substrate, it can be understood as a “docking site” for the keratin network to the substrate 59 . This incorporation will have two effects.…”
Section: Resultsmentioning
confidence: 99%
“…Talin has also been identified as the most highly expressed integrin-cytoskeleton crosslinker that promotes integrin activation and is associated with increased invasion of cSCC into the adjacent tissue [35]. Talin has also been shown to affect hemidesmosomal-like anchorage of keratinocytes and influence keratin network organization, including keratin filament bundling and nucleation in epithelial cancer cells [43]. Data presented here suggest that Flii may increase talin expression in cSCC to upregulate K14 signaling; however, further research is required to understand the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Moreover, after moderate modification, keratin could be applied in clinical use, [15,16] which is divided into cytoskeleton intermediate filament protein. [17,18] It was also found that the mixing of keratin and chitosan could significantly enhance the formation of blood vessels to achieve the effect of nerve repair. [19] As we know, most of the feather keratin (FK) were discarded, resulting in waste of resources and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent biocompatibility, it can be used to prepare keratin membranes, [11,12] nanoparticle scaffolds [13] or pH‐sensitive hydrogen [14] . Moreover, after moderate modification, keratin could be applied in clinical use, [15,16] which is divided into cytoskeleton intermediate filament protein [17,18] . It was also found that the mixing of keratin and chitosan could significantly enhance the formation of blood vessels to achieve the effect of nerve repair [19] …”
Section: Introductionmentioning
confidence: 99%